EntE, EntS and TolC synergistically contributed to the pathogenesis of APEC strain E058. (April 2020) - Mu, Xiaohui; Gao, Ruxia; Xiao, Wenhua; Gao, Qingqing; Cao, Chunguang; Xu, Huiqinq; Gao, Song; Liu, Xiufan
Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) shows an enhanced ability to cause infection outside the intestinal tract. Avian pathogenic E. coli (APEC), one type of ExPEC, causes avian colibacillosis, a disease of significant economic importance to poultry producers worldwide that is characterized by systemic infection. Some ExPEC strains as well as other pathogenic enterobacteria produce enterobactin, a catecholate siderophore used to sequester iron during infection. Here, we showed that disruption of enterobactin efflux via outer membrane protein TolC significantly decreased the pathogenicity of APEC strain E058. Furthermore, colonization and persistence assays performed using a chicken infection model showed that the Δ tolC mutant was obviously attenuated ( p ˂0.001). In contrast, disruption of enterobactin synthesis gene entE and/or the inner membrane transporter gene entS had little effect on pathogenicity. Analysis of growth kinetics revealed a significant reduction in the growth of triple mutant strain E058Δ entE Δ entS Δ tolC in iron-deficient medium compared with the wild-type strain ( p ˂0.001), while no growth impairment was noted for the E058Δ tolC mutant in either Luria-Bertani broth or iron-deficient medium. The E058Δ entE Δ entS Δ tolC mutant also showed significantly decreased virulence compared with single mutant strain E058Δ tolC . Low-copy complementation of strains E058Δ tolC and E058Δ entE Δ entS Δ tolC with plasmid-borne tolC restored virulence to wild-type levels in the chicken infection model. Macrophage infection assays showed that ingestion of E058Δ tolC by macrophage cell line HD11 cells was reduced compared with ingestion of the E058Δ entE Δ entS Δ tolC mutant. However, no significant differences were observed between the mutants and the wild-type in a chicken serum resistance assay. Together, these results suggest that EntE, EntS and TolC synergistically contributed to the pathogenesis of APEC strain E058 in an iron-deficient environment. Highlights: Synergism of entE, entS, and tolC on the growth deficiency of APEC E058 in iron-restricted conditions. entE, entS, and tolC together synergistically contributed to the pathogenesis of APEC. Loss of entE, entS, and/or tolC did not affect serum resistance. Deletion of tolC reduces the macrophage ingestion rate. EntE, EntS, and TolC synergistically enhance APEC ingestion by macrophages.